Identifikasi Penilaian Risiko Kecelakaan Kerja dengan Metode Hazard Identification Risk Assessment and Risk Control (HIRARC) - Damayanti, Dini; Nalhadi, Ahmad (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2017)
In construction activities do not escape from operations on iron, in iron activities cannot be separated from work accidents that often occur. As with work accidents that occur in reinforcing iron manufacturing activities, it is necessary to make further identification to determine the potential for workplace accidents that have not been identified before. Therefore, researchers are interested in identifying further the potential for whatever might occur in reinforcing iron activities at PT Adhi Karya, using the Hazard Identification Risk Assessment and Risk Control (HIRARC) method. HIRARC is a method used to identify, then provide a hazard assessment and control potential workplace accidents in work activities that are being carried out. This research is qualitative research. The purpose of this study was to find out the dominant factors of work accidents in reinforcing iron activities in the Pakupatan-Palima road construction project and to find out the appropriate control proposals to reduce the risk of occupational hazards and provide proper controls to reduce the risk of occupational hazards. In this study, researchers used the HIRARC method. The technique used in data collection is field observation, and interviews. Data analysis begins with calculating the risk value with a score. Based on the results of the study, it is known that there are six types of jobs obtained by the percentage of 30.8% for potential low, 61.5% for likely medium and 7.7% for likely high. To find the root causes and dominant factors of work accidents, researchers using the Root Cause Analysis (RCA) method found that the dominant elements of work accidents in manufacturing activities were factors in human habits that did not use PPE.